RESEPSI SANTRI TERHADAP PEMBACAAN SURAT YASIN DALAM TRADISI ROMANTISAN: STUDI LIVING QUR’AN DI PONDOK PESANTREN AL IHSAN, CIBIRU HILIR, BANDUNG - Abdul Bari; Aleh Hidayat; Amirul Rasyid; Arip Rahmat Nurhidayat; Chynthya Nursyifa Fitri Mulyani; Ecep Ismail; Asep Abdul Muhyi (Adisam Publisher, 2025)
This study examines the santri's reception of the recitation of Surah Yasin in the Romantisan tradition at Pondok Pesantren Al Ihsan, Cibiru Hilir, Bandung, as a form of practicing the Living Qur'an. Using a qualitative approach and Hans Robert Jauss' reception theory, this study identifies three main forms of reception: spiritual, socio-cultural, and personal emotional. Data were obtained through literature review, in-depth interviews, and documentation. The results show that the recitation of Surah Yasin is not just a religious routine, but has become a living and meaningful social practice for santri. This tradition strengthens faith values, strengthens social relationships, and creates deep emotional experiences. Surah Yasin is not only read, but lived in the collective life of the pesantren through a systematic organizational structure and active participation of all santri. Thus, the Qur'an proves to be a text that continues to interact dynamically with people's lives, in accordance with the spirit of the Living Qur'an.